Axillary management for early invasive breast cancer patients: Who will truly benefit? - Liu, Yanbiao; Fan, Yan; Jin, Zining; Cui, Mengyao; Yu, Xinmiao; Jin, Feng; Wang, Xu (Frontiers in Oncology, 2022)
Background The implementation of sentinel lymph node biopsy (SLNB) and further completion axillary lymph node dissection (cALND) after positive sentinel lymph nodes (SLNs) on early invasive breast cancer patients should be cautiously tailored. Identifying predictors for SLN and non-sentinel lymph node (nSLN) metastases can help surgeons make better surgical decisions. Methods A retrospective case-control study was designed and a total of 560 eligible patients were enrolled consecutively. They were all diagnosed in our center and received appropriate medical care. According to the metastasis of SLN and nSLN, they were divided into metastatic and non-metastatic groups on two successive occasions to investigate the relationship between clinical factors, pathological factors, hematological factors and lymph node metastasis. Results In total, 101 (18.04%) patients developed SLN metastases, including 98 patients with macro-metastases and 3 patients with micro-metastases. Out of 97 patients receiving further cALND, 20 patients (20.62%) developed nSLN metastases. Multivariate analysis revealed that “high expression of Ki-67” and “lymphatic invasion” predicted a higher risk of SLN metastasis; and “increased number of positive SLNs” and “increased systemic inflammation index (SII)” predicted a higher risk of nSLN metastasis. Conclusion Surgery for early invasive breast cancer patients should be more customized and precise. Appropriate axillary management is necessary for patients with the associated predictors.